2009
DOI: 10.1002/bdra.20594
|View full text |Cite
|
Sign up to set email alerts
|

Familial recurrence of urethral stenosis/atresia

Abstract: A microdeletion of 6p25.3, identified in mother and one fetus, is not associated with a gene known to be involved in urethral development and therefore of unknown significance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…The two theories are not mutually exclusive. In the distension sequence model, impairment of bladder emptying, due to mechanical or functional anomalies, distends the abdominal wall, which in turn leads to hypoplasia/atrophy of the striated muscles of the anterior abdominal wall [Shimada et al, 2000;Siebert and Walker, 2009]. Experimental evidence exists for this mechanical model: ligation of the urethra in lamb fetuses results in renal dysplasia and hypoplasia of the abdominal wall muscles, with a wrinkled appearance of the abdomen [Gonzalez et al, 1990].…”
Section: Introductionmentioning
confidence: 98%
“…The two theories are not mutually exclusive. In the distension sequence model, impairment of bladder emptying, due to mechanical or functional anomalies, distends the abdominal wall, which in turn leads to hypoplasia/atrophy of the striated muscles of the anterior abdominal wall [Shimada et al, 2000;Siebert and Walker, 2009]. Experimental evidence exists for this mechanical model: ligation of the urethra in lamb fetuses results in renal dysplasia and hypoplasia of the abdominal wall muscles, with a wrinkled appearance of the abdomen [Gonzalez et al, 1990].…”
Section: Introductionmentioning
confidence: 98%
“…The two theories are not mutually exclusive. In the distension sequence model, impairment of bladder emptying, due to mechanical or functional anomalies, distends the abdominal wall, which in turn leads to hypoplasia/atrophy of the striated muscles of the anterior abdominal wall [Shimada et al, 2000; Siebert and Walker, 2009]. Experimental evidence exists for this mechanical model: ligation of the urethra in lamb fetuses results in renal dysplasia and hypoplasia of the abdominal wall muscles, with a wrinkled appearance of the abdomen [Gonzalez et al, 1990].…”
Section: Introductionmentioning
confidence: 99%
“…This case represents a rare situation in which fetal urethral stenosis was suspected because of familial history, and was confirmed by fetal cystoscopy. It is rare that there is a family history of the condition in fetuses with lower urinary tract obstruction (LUTO), although Siebert et al 5 reported a case of familial recurrence of urethral stenosis/atresia. In our case familial history led us to anticipate a potential situation of fetal urethral stenosis and to plan for the possibility of placing a transurethral stent.…”
Section: Discussionmentioning
confidence: 99%